Reactive oxygen species in sarcopenia: Should we focus on excess oxidative damage or defective redox signalling?. (August 2016) - Jackson, Malcolm J.
Abstract: Physical frailty in the elderly is driven by loss of muscle mass and function and hence preventing this is the key to reduction in age-related physical frailty. Our current understanding of the key areas in which ROS contribute to age-related deficits in muscle is through increased oxidative damage to cell constituents and/or through induction of defective redox signalling. Recent data have argued against a primary role for ROS as a regulator of longevity, but studies have persistently indicated that aspects of the aging phenotype and age-related disorders may be mediated by ROS. There is increasing interest in the effects of defective redox signalling in aging and some studies now indicate that this process may be important in reducing the integrity of the aging neuromuscular system. Understanding how redox-signalling pathways are altered by aging and the causes of the defective redox homeostasis seen in aging muscle provides opportunities to identify targeted interventions with the potential to slow or prevent age-related neuromuscular decline with a consequent improvement in quality of life for older people.